Caring for Pregnant Patients with COVID-19: Practical Tips Getting from Policy to Practice - London, Viktoriya; McLaren, Rodney, Jr.; Stein, Janet; Atallah, Fouad; Fisher, Nelli; Haberman, Shoshana; McCalla, Sandra; Minkoff, Howard (American Journal of Perinatology, 2020)
Novel coronavirus disease 2019 (COVID-19) is a pandemic with most American cases in New York. As an institution residing in a high-prevalence zip code, with over 8,000 births annually, we have cared for over 80 COVID-19-infected pregnant women, and have encountered many challenges in applying new national standards for care. In this article, we review how to change outpatient and inpatient practices, develop, and disseminate new hospital protocols, and we highlight the psychosocial challenges for pregnant patients and their providers.Key Points
Keywords: COVID-19; labor and delivery; novel coronavirus; psychosocial challenges; universal testing